Assessment of the Nature of Reproduction Processes in Rural Municipalities (districts) of the Region of Buryatia - Chimitdorgieva, Ekaterina Tsyrenzhabovna; Vanchikova, Elena Nikolaevna; Tsyrenov, Dashi Dashanimaevich; Munkueva, Irina Sergeevna; Malishevdashi-tsyrenov@mail.ru, Evgeniy Anatolévich (International Review of Management and Marketing, 2016)
The article examines the nature of reproduction processes in rural municipalities (districts) in the region of Buryatia. It is supposed that the higher the level of socio-economic development of municipal districts, the higher the return from the resources used there. The study, based on the assessment of elasticity, has found that a high level of economic development of the municipality does not correlate with indicators of high return from the factors of production. Keywords: fixed capital, investment, employment, economic development, municipalities of the region, elasticity JEL Classifications: R00, R58, O47